Human Resource Development Affecting in Operation Competency of Production Supervisor in Food Industry - Detnakarin, Prasit; Sirivisitkul, Sanit; Janma, Chaiwut (Dusit Thani College Journal, 2020)
The objectives of the study were to examine in operation competency of production supervisor in food industry in terms of the human resource development factors for forecast effect to in operation competency, survey research was applied. A sample was selected from 220 person of production supervisor in seasoning or food ingredients industry and applying the Krejci and Morgan formula in determining the sample groups to calculate at 95% confidence interval. Research tool was quantitative questionnaire, Statistics including’s average value, standard deviation and multiple regression analysis. The results of the study were as follows, production supervisor in food industry had overall in operation competency at high level, average 3.50, in which the core competency had the highest mean score, followed by functional competency and management competency corresponding, human resource development factors (training, career development, organization development) had positive influent to current competency of production supervisor 32.5 percent was statistically at 0.01 level